Extreme-environment-resistant non-isocyanate polyurethane adhesive and preparation method thereof

By introducing rigid structure and adjusting reaction conditions into non-isocyanate polyurethane adhesives, the problem of insufficient performance in extreme environments is solved, and high bond strength and solvent resistance are improved, and it is suitable for aerospace and medical fields.

CN119144265AActive Publication Date: 2024-12-17DALIAN UNIV OF TECH

Patent Information

Application Number
CN202411401363.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2024-12-17
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

The existing non-isocyanate polyurethane adhesives have insufficient performance in extreme environments, especially their high temperature resistance and low solvent resistance, which limits their application in high-tech fields such as aerospace.

Method used

The phenolic compounds containing rigid groups react with carbon dioxide to form a five-membered cyclic carbonate monomer, and react with flexible segment amines and rigid segment amines to prepare a non-isocyanate polyurethane adhesive that resists extreme environments. By adjusting the reaction conditions and molar ratio to improve the mechanical properties of the material and solvent resistance.

Benefits of technology

It realizes that high bond strength can be maintained in extreme environments (such as low temperature and high temperature), and can maintain high overlap shear strength after soaking in solvents, significantly improving the solvent resistance of the material, suitable for aviation equipment and Medical devices and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144265A_ABST
    Figure CN119144265A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of preparation of non-isocyanate polyurethane, and particularly relates to a preparation method of an extreme-environment-resistant non-isocyanate polyurethane adhesive, which comprises the following steps: preparing a cyclic carbonate monomer containing a rigid structure, selecting the type of di / polyamine, and adjusting the ratio of a flexible chain segment amine compound to a rigid amine compound, thereby obtaining the extreme-environment-resistant non-isocyanate polyurethane adhesive. A series of non-isocyanate polyurethane adhesives with excellent mechanical properties are prepared, and controllability of bonding strength and extreme environment resistance is realized. The adhesive disclosed by the invention is simple in synthesis method, reaction conditions are easy to control, and the lap joint shear strength of bonded Al can reach 16.7 MPa; the lap joint shear strength at the low temperature of-196 DEG C reaches 15.6 MPa; and the overlapping shear strength at the high temperature of 190 DEG C reaches 15.2 MPa. After a bonded sample is soaked in a solvent for 24 h, the lap shear strength can still be maintained at 15.4 MPa or above and can reach 16.5 MPa, and the adhesive can be widely applied to the fields of aerospace, medical instruments, chemical product packaging and the like and has good market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of non-isocyanate polyurethane, and particularly relates to an extreme environment resistant non-isocyanate polyurethane adhesive and a preparation method thereof. Background Art

[0002] Adhesives for aerospace are key materials in the manufacture of high-tech products such as launch vehicles, satellites, and spacecraft. These aerospace equipment must face severe challenges in extreme environments during launch, orbital operation, and recovery. High acceleration and severe vibration during launch, ultra-low and ultra-high temperature cycles after entering space, material stability under high vacuum conditions, and exposure to unique environments such as space radiation and micrometeorite impacts make it difficult for ordinary adhesives to cope with the requirements. Therefore, extreme environment resistant adhesives have become a major key technical problem that cannot be avoided and must be properly solved in the research and development of high-tech equipment such as aerospace, and have important scientific significance.

[0003] As a new type of polyurethane material, non-isocyanate polyurethane (NIPU) has received increasing attention in recent years. Compared with traditional polyurethane adhesives, NIPU has some unique advantages, one of which is that it does not use toxic and moisture-sensitive isocyanate monomers, which is the main problem faced by polyurethane during synthesis, transportation and storage. NIPU is prepared by addition polymerization of cyclic carbonates and amine compounds, producing a large number of hydroxyl groups on the polymer backbone. These hydroxyl groups can form intermolecular and intramolecular hydrogen bonds, and the abundant hydrogen bonds can produce more interactions with the substrate surface, so that NIPU has excellent tensile strength and lap shear strength. The patent application with publication number CN 117586499 A discloses a resveratrol-based non-isocyanate polyurethane adhesive, and a lap plate is prepared with stainless steel as the substrate, in which the sample CREPP-1.0 (9.2MPa) reaches the maximum. The patent application with publication number CN 117363297 A discloses a high-performance non-isocyanate polyurethane adhesive material, which can achieve bonding, repair and protection of various substrates in ultra-low temperature environments. In ultra-low temperature (liquid nitrogen, -196°C) environment, the bonding strength to steel plates exceeds 14MPa, and the bonding strength to aluminum alloys exceeds 11MPa.

[0004] As mentioned above, although NIPU has been widely studied in the field of adhesives, the bonding strength has not reached the level required for application in some special fields, and the mechanical properties of NIPU are relatively low, which limits its application in adhesives resistant to extreme environments, such as high temperature resistance, solvent resistance, etc. Therefore, it is urgent to develop a method for preparing a non-isocyanate polyurethane resistant to extreme environments. Summary of the invention

[0005] In view of the problem that the adhesive in the prior art has poor extreme environment resistance performance, the present invention provides an extreme environment resistant non-isocyanate polyurethane adhesive and a preparation method thereof.

[0006] In a first aspect, the present invention provides a method for preparing an extreme environment resistant non-isocyanate polyurethane adhesive, wherein a diglycidyl ether intermediate is synthesized using a rigid group-containing phenolic compound as a raw material, and then reacted with carbon dioxide to obtain a five-membered cyclic carbonate monomer, and finally reacted with a flexible segment amine compound and a rigid segment amine compound to obtain the extreme environment resistant non-isocyanate polyurethane adhesive;

[0007] The rigid group-containing phenolic compound is selected from one of magnolol, resveratrol and genistein;

[0008] The flexible segment amine compound is selected from a triamine compound containing a polyether structure with a molecular weight of 400-600 or a long carbon chain diamine compound; the rigid segment amine compound is selected from a short carbon chain triamine compound with a molecular weight of 100-200 and a diamine compound containing a six-membered aliphatic ring.

[0009] Furthermore, the flexible segment amine compound is selected from at least one of Priamine 1074, Priamine 1075, and polyetheramine T403, and the rigid segment amine compound is selected from at least one of 1,8-diamino-p-menthane (MDA), isophoronediamine (IPDA), and tris(2-aminoethyl)amine (TAEA).

[0010] Furthermore, the molar amount of amino groups in the flexible segment amine compound accounts for 20%-95% of the total molar amount of amino groups in the flexible segment amine compound and the rigid segment amine compound.

[0011] Furthermore, the molar ratio of the cyclic carbonate in the five-membered cyclic carbonate monomer to the total amount of amino groups in the flexible segment amine compound and the rigid segment amine compound is 1:1.

[0012] Furthermore, the rigid group-containing phenolic compound is magnolol, the flexible segment amine compound is selected from tertiary amine compounds with a molecular weight of 400-600 containing a polyether structure, and the rigid segment amine compound is selected from short carbon chain tertiary amine compounds with a molecular weight of 100-200.

[0013] Further, the following steps are included:

[0014] S1, stirring a phenolic compound containing a rigid group and epichlorohydrin to react under the action of a first catalyst, and then adding a sodium hydroxide aqueous solution to continue the reaction to obtain a diglycidyl ether intermediate;

[0015] S2, dissolving the diglycidyl ether intermediate prepared in step S1, the second catalyst, and the co-catalyst in a solvent, placing the mixture in a high-pressure reactor, and reacting the mixture under the condition of introducing CO2 to obtain a five-membered cyclic carbonate monomer;

[0016] S3, dissolving the five-membered cyclic carbonate monomer prepared in step S2, the flexible segment amine compound, and the rigid segment amine compound in a solvent in proportion for prepolymerization, and obtaining an extreme environment resistant non-isocyanate polyurethane adhesive through post-treatment.

[0017] Furthermore, the first catalyst in step S1 is at least one of benzyltriethylammonium chloride, tetrabutylammonium chloride and tetrabutylammonium bromide.

[0018] Furthermore, the molar ratio of the phenolic hydroxyl content in the phenolic compound containing rigid groups to the first catalyst is 1:0.05-0.1; the molar ratio of the phenolic hydroxyl content in the phenolic compound containing rigid groups to epichlorohydrin is 1:20-25, and the molar ratio of the phenolic hydroxyl content in the phenolic compound containing rigid groups to sodium hydroxide is 1:1-1.2.

[0019] Furthermore, the stirring reaction conditions in step S1 are 80-100° C. for 2-4 hours, then cooled to room temperature, 40 wt % sodium hydroxide aqueous solution is added through a constant pressure funnel, and the reaction is continued for 1-12 hours.

[0020] Furthermore, the second catalyst in step S2 is one of tetrabutylammonium iodide, tetrabutylammonium bromide and tetrabutylammonium chloride, the co-catalyst is L-ascorbic acid; and the solvent is one of N-methylpyrrolidone, acetone and butanone.

[0021] Furthermore, the molar ratio of the epoxy group of the diglycidyl ether intermediate to the second catalyst is 1:0.02-0.04, and the molar ratio of the epoxy group of the diglycidyl ether intermediate to the co-catalyst is 1:0.01-0.02.

[0022] Furthermore, the reaction conditions in step S2 are pressure 2-4 MPa, 80° C., and reaction time 24-48 h.

[0023] Furthermore, the prepolymerization reaction conditions in step S3 are 70-90° C. for 1-3 hours.

[0024] Furthermore, the solvent in step S3 is at least one of anhydrous chloroform, anhydrous dimethylacetamide (DMAc), anhydrous dimethylformamide (DMF), and anhydrous dimethyl sulfoxide (DMSO).

[0025] Furthermore, the diglycidyl ether in step S1 is post-treated by washing with water, retaining the organic phase, and then drying with anhydrous magnesium sulfate, filtering, rotary evaporation and vacuum drying.

[0026] Furthermore, after the reaction in step S2 is completed, the organic phase is retained after washing and filtering to obtain the five-membered cyclic carbonate monomer.

[0027] Furthermore, the post-processing method of step S3 is: transferring the reaction mixture to a polytetrafluoroethylene mold to volatilize the solvent and solidify it.

[0028] Furthermore, the curing reaction conditions of step S3 are: volatilize the solvent at 50-70°C for 12-24 hours, further volatilize the solvent and cure at 90-100°C for 12-24 hours, and cure at 150°C for 12-24 hours.

[0029] In the second aspect, the present invention discloses a type of extreme environment resistant non-isocyanate polyurethane adhesive, which is prepared by the above preparation method. Its extreme environment resistance performance is that the lap shear strength of Al bonding can reach 16.7MPa; the lap shear strength reaches 15.6MPa in a low temperature environment of -196°C; the lap shear strength reaches 15.2MPa in a high temperature environment of 190°C; after the bonding sample is immersed in a solvent for 24 hours, the lap shear strength can still be maintained above 15.4MPa, and can reach 16.5MPa.

[0030] The material prepared by the present invention can be applied in the field of aviation equipment to maintain the normal operation of electronic equipment in high-altitude and low-temperature environments. In extreme temperature environments, it ensures the stable connection of various components to ensure flight safety. It can also be applied to medical equipment to manufacture medical equipment and instruments that need to be frequently disinfected or exposed to chemical reagents to ensure the stability of the bonding parts. It can also be applied to chemical product packaging to package products that need to contact solvents to ensure that the packaging materials will not become ineffective due to contact with solvents during transportation and storage.

[0031] Beneficial effects:

[0032] 1. The synthesis method of the present invention is simple and the reaction conditions are easy to control. By preparing a cyclic carbonate monomer containing a rigid structure, selecting the type of di / polyamine and adjusting the ratio of the flexible segment amine compound and the rigid amine compound, a non-isocyanate polyurethane adhesive with excellent mechanical properties is prepared to achieve controllability of bonding strength and resistance to extreme environments. The introduction of the rigid structure can not only enhance the cohesive energy of the material, but also enhance the solvent resistance of the material. The rigid structure makes it more difficult for the molecular chain to rotate and bend, and the molecular chains are arranged more closely. Due to the small gap between the molecular chains, it is difficult for solvent molecules to penetrate into the interior of the material, thereby improving the solvent resistance of the material. A part of the molecular structure of the prepared material is composed of soft segments (the main chain contains carbon-carbon bonds, ether bonds, etc.), which has good flexibility. It and the rigid groups in the structure work synergistically to achieve high-performance adhesives with bonding strength and resistance to extreme environments.

[0033] 2. The non-isocyanate polyurethane adhesive provided by the present invention has more interactions with the substrate surface through abundant hydrogen bonds and polar groups, and combined with the high cohesive energy of the material itself, it exhibits excellent performance. The material has excellent tensile strength, lap shear strength, high and low temperature resistance, and solvent resistance. Among them, the lap shear strength when bonding aluminum can reach 16.7MPa; the lap shear strength of the material reaches 15.6MPa after being treated in a low temperature environment (-196°C) for 24 hours; the lap shear strength reaches 15.2MPa after being treated in a high temperature environment (190°C) for 30 minutes. After the bonding sample is immersed in a solvent (acetone, DMF, ether, ethyl acetate, n-hexane, tetrahydrofuran, toluene) for 24 hours, the lap shear strength can still be maintained above 15.4MPa, and can reach 16.5MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 MAG-T403 prepared in Example 2 30 MDA 70 Infrared spectrum of

[0035] Figure 2 RE-1074 prepared in Example 5 70 MDA 30 Infrared spectrogram;

[0036] Figure 3 Gen-1075 prepared in Example 8 80 IPDA 20 Infrared spectrum of

[0037] Figure 4 RE-1074 prepared in Example 5 70 MDA 30 Tensile shear diagram. DETAILED DESCRIPTION

[0038] In order to more clearly understand the above-mentioned purposes, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only part of the embodiments of the present invention, not all of the embodiments.

[0039] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0040] The experimental methods and calculation methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified. Performance testing instruments used in the examples of the present invention: Microstructures were analyzed using a Fourier transform infrared spectrometer.

[0041] In order to test its performance as an adhesive, aluminum was selected as the bonding object. Before bonding, the aluminum was smoothed with sandpaper. Then, the NIPU material was cut into rectangles (25×12.5×0.1mm) and placed between two identical substrates (100×25×2mm) with an overlap area of ​​25mm×12.5mm. Subsequently, this sandwich-shaped sample was hot-pressed in a hot press (190℃, 10min, 0.5MPa). After cooling to room temperature and leaving for 12 hours, a uniaxial tensile test was carried out at a strain rate of 5mm / min at 20℃ to determine the overlap shear strength. The tensile shear strength test was carried out according to GB / T 7124-2008 to evaluate its bonding strength.

[0042] High temperature resistant specimens: The bonded specimens were baked with a heat gun to 190°C for 30 minutes, and then subjected to a tensile bonding strength test.

[0043] Low temperature resistant specimens: Place the bonded specimens in liquid nitrogen for 24 hours and then perform a tensile bond strength test.

[0044] Solvent resistant specimens: The bonded specimens were immersed in organic solvents for 24 hours and then subjected to tensile bond strength tests.

[0045] Embodiment 1

[0046] (1) Preparation of magnolol epoxy resin (MAG-EP)

[0047] Add magnolol (20 g, 75.2 mmol, 1 eq) and benzyltriethylammonium chloride (3.4 g, 14.9 mmol, 0.1 eq) into a 500 mL three-necked flask under nitrogen atmosphere. Then add epichlorohydrin (276.6 g, 3006.5 mmol, 40 eq), heat to 80 ° C to form a clear solution, and stir for 4 hours;

[0048] Then the temperature was lowered to room temperature, 40wt% NaOH solution (11.8mL, 165.4mmol, 2.2eq) was added dropwise using a constant pressure funnel, and after reacting for 1h, the mixture was filtered to remove salt, washed with water 3 times, and the organic phase was taken, and then dried by adding anhydrous magnesium sulfate, filtered, and the epichlorohydrin was removed by rotary evaporation, and vacuum dried at 60°C for 24h to obtain a white powder. The yield was 94%.

[0049] (2) Preparation of magnolol five-membered cyclic carbonate (MAG-BCC)

[0050] MAG-EP (20 g, 52.9 mmol, 1 eq), tetrabutylammonium iodide (0.78 g, 2.1 mmol, 0.04 eq) and L-ascorbic acid (0.19 g, 1.08 mmol, 0.02 eq) were dissolved in acetone, added to a high-pressure reactor, introduced with 2 MPa of CO2, reacted at 80°C for 24 h, and after the reaction, the reaction solution was dripped into deionized water, stirred overnight, washed with water three times, and then freeze-dried for 24 h to obtain MAG-BCC. The yield was 91%.

[0051] (3) Preparation of magnolol non-isocyanate polyurethane (MAG-PHU)

[0052] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 80% of the total content. MAG-BCC (0.5 g, 1.1 mmol, 1 eq), TAEA (0.086 g, 0.59 mmol, 0.53 eq), and Priamine 1075 (0.12 g, 0.22 mmol, 0.2 eq) were added to a single-mouth bottle, dissolved with anhydrous chloroform and anhydrous DMAc, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50°C for 12 h, cured at 90°C for 24 h, and cured at 150°C for 24 h, to obtain MAG-TAEA. 80 1075 20 .

[0053] Example 2

[0054] (1) Preparation of magnolol epoxy resin (MAG-EP)

[0055] Same as Example 1(1).

[0056] (2) Preparation of magnolol five-membered cyclic carbonate (MAG-BCC)

[0057] Same as Example 1(2).

[0058] (3) Preparation of magnolol non-isocyanate polyurethane (MAG-PHU)

[0059] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 70% of the total content. MAG-BCC (0.5 g, 1.1 mmol, 1 eq), T403 (0.097 g, 0.22 mmol, 0.2 eq), and MDA (0.13 g, 0.77 mmol, 0.7 eq) were added to a single-mouth bottle, dissolved with anhydrous chloroform and anhydrous DMAc, prepolymerized at 80 ° C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50 ° C for 12 h, cured at 90 ° C for 24 h, and cured at 150 ° C for 24 h, to obtain MAG-T403. 30 MDA 70 .

[0060] Example 3

[0061] (1) Preparation of magnolol epoxy resin (MAG-EP)

[0062] Same as Example 1(1).

[0063] (2) Preparation of magnolol five-membered cyclic carbonate (MAG-BCC)

[0064] Same as Example 1(2).

[0065] (3) Preparation of magnolol non-isocyanate polyurethane (MAG-PHU)

[0066] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 20% of the total content. MAG-BCC (0.5 g, 1.1 mmol, 1 eq), T403 (0.258 g, 0.59 mmol, 0.53 eq), and IPDA (0.037 g, 0.22 mmol, 0.2 eq) were added to a single-mouth bottle, dissolved with anhydrous chloroform and anhydrous DMAc, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50°C for 12 h, cured at 90°C for 24 h, and cured at 150°C for 24 h, to obtain MAG-T403. 80 IPDA 20 .

[0067] Example 4

[0068] (1) Preparation of resveratrol epoxy resin (RE-EP)

[0069] Add resveratrol (20 g, 87.7 mmol, 0.3 eq) and tetrabutylammonium chloride (3.65 g, 13.1 mmol) into a 500 mL three-necked flask under nitrogen atmosphere. Then add epichlorohydrin (605 g, 6576.1 mmol, 75 eq), heat to 90°C to form a clear solution, and stir for 3 hours;

[0070] Then the temperature was lowered to room temperature, and 40wt% NaOH solution (24.4mL, 342.0mmol, 3.9eq) was added dropwise using a constant pressure funnel. After reacting for 1h, the mixture was filtered to remove salt, washed with water 3 times, and the organic phase was taken. Anhydrous magnesium sulfate was added to dry the mixture, filtered, and epichlorohydrin was removed by rotary evaporation. The mixture was dried under vacuum at 60°C for 24h to obtain a white powder. The yield was 93%.

[0071] (2) Preparation of resveratrol five-membered cyclic carbonate (RE-TCC)

[0072] RE-EP (20 g, 50.5 mmol, 1 eq), tetrabutylammonium bromide (1.95 g, 6.0 mmol, 0.12 eq) and L-ascorbic acid (0.53 g, 3.01 mmol, 0.06 eq) were dissolved in acetone, added to a high-pressure reactor, introduced with 3 MPa of CO2, reacted at 100°C for 12 h, and after the reaction, the reaction solution was dripped into deionized water, stirred overnight, washed with water three times, and then freeze-dried for 24 h to obtain RE-TCC. The yield was 92%.

[0073] (3) Preparation of resveratrol non-isocyanate polyurethane (RE-PHU)

[0074] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 10% of the total content. RE-BCC (0.5 g, 0.947 mmol, 1 eq), Priamine 1074 (0.683 g, 1.28 mmol, 1.35 eq), and IPDA (0.024 g, 0.14 mmol, 0.15 eq) were added to a single-mouth bottle, dissolved with anhydrous DMF, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold. After volatilization at 70°C for 24 h, curing at 100°C for 12 h, and curing at 150°C for 12 h, RE-1074 was obtained. 90 IPDA 10 .

[0075] Example 5

[0076] (1) Preparation of resveratrol epoxy resin (RE-EP)

[0077] Same as Example 4(1).

[0078] (2) Preparation of resveratrol five-membered cyclic carbonate (RE-TCC)

[0079] Same as Example 4(2).

[0080] (3) Preparation of resveratrol non-isocyanate polyurethane (RE-PHU)

[0081] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 30% of the total content. RE-BCC (0.5 g, 0.947 mmol, 1 eq), Priamine 1074 (0.531 g, 0.994 mmol, 1.05 eq), and MDA (0.073 g, 0.426 mmol, 0.45 eq) were added to a single-mouth bottle, dissolved with anhydrous DMF, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold. After volatilization at 50°C for 12 h, curing at 90°C for 24 h, and curing at 150°C for 24 h, RE-1074 was obtained. 70 IPDA 30 .

[0082] Example 6

[0083] (1) Preparation of resveratrol epoxy resin (RE-EP)

[0084] Same as Example 4(1).

[0085] (2) Preparation of resveratrol five-membered cyclic carbonate (RE-TCC)

[0086] Same as Example 4(2).

[0087] (3) Preparation of resveratrol non-isocyanate polyurethane (RE-PHU)

[0088] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 80% of the total content. RE-BCC (0.5 g, 0.947 mmol, 1 eq), Priamine 1075 (0.159 g, 0.284 mmol, 0.3 eq), and MDA (0.193 g, 1.136 mmol, 1.2 eq) were added to a single-mouth bottle, dissolved with anhydrous DMF, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50°C for 12 h, cured at 90°C for 24 h, and cured at 150°C for 24 h, to obtain RE-1075. 20 MDA 80 .

[0089] Example 7

[0090] (1) Preparation of genistein epoxy resin (Gen-EP)

[0091] Genistein (20 g, 73.9 mmol, 1 eq) and tetrabutylammonium bromide (4.29 g, 13.3 mmol, 0.21 eq) were added to a 500 mL three-necked flask under nitrogen atmosphere. Then epichlorohydrin (470.1 g, 5109.8 mmol, 69 eq) was added, heated to 100°C to form a clear solution, and stirred for 2 h.

[0092] Then lower the temperature to room temperature, add 40wt% NaOH solution (18.1mL, 266.0mmol, 3.6eq) dropwise with a constant pressure funnel, react for 1h, filter to remove salt, wash with water 3 times, take the organic phase, add anhydrous magnesium sulfate to dry, filter, remove epichlorohydrin by rotary evaporation, and dry under vacuum at 60℃ for 24h to obtain a white powder. Yield 90%.

[0093] (2) Preparation of Genistein Pentacyclic Carbonate (Gen-TCC)

[0094] Gen-EP (20 g, 45.6 mmol, 1 eq), tetrabutylammonium chloride (1.14 g, 4.1 mmol, 0.09 eq) and L-ascorbic acid (0.36 g, 2.0 mmol, 0.045 eq) were dissolved in acetone, added to a high-pressure reactor, introduced with 4 MPa of CO2, reacted at 90°C for 20 h, and after the reaction, the reaction solution was dropped into deionized water, stirred overnight, washed with water three times, and then freeze-dried for 24 h to obtain Gen-TCC. The yield was 92%.

[0095] (3) Preparation of Genistein Non-isocyanate Polyurethane (Gen-PHU)

[0096] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 5% of the total content. Gen-BCC (0.5 g, 0.877 mmol, 1 eq), Priamine 1075 (0.700 g, 1.250 mmol, 1.425 eq), and IPDA (0.011 g, 0.066 mmol, 0.075 eq) were added to a single-mouth bottle, dissolved with anhydrous DMSO, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold. After volatilization at 60°C for 16 h, curing at 95°C for 24 h, and curing at 150°C for 20 h, Gen-1075 was obtained. 95 IPDA5.

[0097] Example 8

[0098] (1) Preparation of genistein epoxy resin (Gen-EP)

[0099] Same as Example 7(1).

[0100] (2) Preparation of Genistein Pentacyclic Carbonate (Gen-TCC)

[0101] Same as Example 7(2).

[0102] (3) Preparation of Genistein Non-isocyanate Polyurethane (Gen-PHU)

[0103] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 20% of the total content. Gen-BCC (0.5 g, 0.877 mmol, 1 eq), Priamine 1074 (0.563 g, 1.052 mmol, 1.2 eq), and IPDA (0.045 g, 0.263 mmol, 0.3 eq) were added to a single-mouth bottle, dissolved with anhydrous DMSO, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold. After volatilization at 50°C for 12 h, curing at 90°C for 24 h, and curing at 150°C for 24 h, Gen-1075 was obtained. 80 IPDA 20 .

[0104] Example 9

[0105] (1) Preparation of genistein epoxy resin (Gen-EP)

[0106] Same as Example 7(1).

[0107] (2) Preparation of Genistein Pentacyclic Carbonate (Gen-TCC)

[0108] Same as Example 7(2).

[0109] (3) Preparation of Genistein Non-isocyanate Polyurethane (Gen-PHU)

[0110] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 70% of the total content. Gen-BCC (0.5 g, 0.877 mmol, 1 eq), Priamine 1074 (0.211 g, 0.395 mmol, 0.45 eq), and MDA (0.157 g, 0.921 mmol, 1.05 eq) were added to a single-mouth bottle, dissolved with anhydrous DMSO, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold. After volatilization at 50°C for 12 h, curing at 90°C for 24 h, and curing at 150°C for 24 h, Gen-1074 was obtained. 30 MDA 70 .

[0111] Comparative Example 1

[0112] (1) Preparation of magnolol epoxy resin (MAG-EP)

[0113] Same as Example 1(1).

[0114] (2) Preparation of magnolol five-membered cyclic carbonate (MAG-BCC)

[0115] Same as Example 1(2).

[0116] (3) Preparation of magnolol non-isocyanate polyurethane (MAG-PHU)

[0117] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino content of rigid segment amine accounted for 100% of the total content. MAG-BCC (0.5 g, 1.1 mmol, 1 eq) and TAEA (0.107 g, 0.733 mmol, 0.667 eq) were added to a single-mouth bottle, dissolved with anhydrous chloroform and anhydrous DMAc, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50°C for 12 h, cured at 90°C for 24 h, and cured at 150°C for 24 h, to obtain MAG-TAEA.

[0118] Comparative Example 2

[0119] (1) Preparation of resveratrol epoxy resin (RE-EP)

[0120] Same as Example 4(1).

[0121] (2) Preparation of resveratrol five-membered cyclic carbonate (RE-TCC)

[0122] Same as Example 4(2).

[0123] (3) Preparation of resveratrol non-isocyanate polyurethane (RE-PHU)

[0124] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino content of rigid segment amine accounted for 0% of the total content. RE-BCC (0.5 g, 0.947 mmol, 1 eq) and Priamine 1075 (0.795 g, 1.420 mmol, 1.5 eq) were added to a single-mouth bottle, dissolved with anhydrous DMF, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50°C for 12 h, cured at 90°C for 24 h, and cured at 150°C for 24 h, to obtain RE-1075.

[0125] Comparative Example 3

[0126] (1) Preparation of genistein epoxy resin (Gen-EP)

[0127] Same as Example 7(1).

[0128] (2) Preparation of Genistein Pentacyclic Carbonate (Gen-TCC)

[0129] Same as Example 7(2).

[0130] (3) Preparation of Genistein Non-isocyanate Polyurethane (Gen-PHU)

[0131] The molar ratio of amino group to cyclic carbonate was controlled to be 1:1, and the amino group content of rigid segment amine accounted for 100% of the total content. Gen-BCC (0.5 g, 0.877 mmol, 1 eq) and MDA (0.224 g, 0.315 mmol, 1.5 eq) were added to a single-mouth bottle, dissolved with anhydrous DMSO, prepolymerized at 80°C for 3 h, and then poured into a polytetrafluoroethylene mold, volatilized at 50°C for 12 h, cured at 90°C for 24 h, and cured at 150°C for 24 h, to obtain Gen-MDA.

[0132] Characterization Example 1

[0133] The cyclic carbonate monomers in Examples 2, 5, and 8 and the prepared NIPU materials were tested by infrared spectroscopy. The infrared spectra obtained showed Figure 1 , Figure 2 and Figure 3 Due to the ring opening of the cyclocarbonate group, the 1795 cm -1 The absorption peak at 1690 cm -1 The absorption peak of C=O appeared at . These results prove the successful preparation of NIPU material.

[0134] Table 1 Lap shear strength of the prepared examples

[0135]

[0136] It can be seen from the results in Table 1 that the bonding strength of the NIPU adhesive provided by the present invention can withstand extreme environments, the bonding strength is above 9MPa, and can reach 16MPa, with excellent bonding performance, excellent high and low temperature resistance and solvent resistance, wherein the low temperature resistance is -196°C, the high temperature resistance is 190°C, and it is resistant to organic solvents. In the high and low temperature resistance test and the solvent resistance test, the bonding performance of the material is only slightly reduced and still maintains a good bonding strength of more than 9MPa. However, the bonding strength provided by Comparative Examples 1, 2, and 3 is relatively low, and the low temperature resistance is poor. For example, in Comparative Example 3, the room temperature bonding strength is 10.9MPa, which is reduced to 6.8MPa after the low temperature resistance test. This is mainly because the material is too brittle, the tensile strength is too high, but the elongation at break is too low, only 5%, which greatly reduces the low temperature resistance of the material.

[0137] It is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the specification of the present invention, or directly or indirectly applied in other related technical fields, is also included in the patent protection scope of the present invention.

Claims

1. A method for preparing an extreme environment resistant non-isocyanate polyurethane adhesive, characterized in that: A diglycidyl ether intermediate is synthesized using a rigid group-containing phenolic compound as a raw material, which is then reacted with carbon dioxide to obtain a five-membered cyclic carbonate monomer, and finally the non-isocyanate polyurethane adhesive resistant to extreme environments is obtained by co-reacting with a flexible segment amine compound and a rigid segment amine compound; The rigid group-containing phenolic compound is selected from one of magnolol, resveratrol and genistein; The flexible segment amine compound is selected from a triamine compound containing a polyether structure with a molecular weight of 400-600 or a long carbon chain diamine compound; the rigid segment amine compound is selected from a short carbon chain triamine compound with a molecular weight of 100-200 or a diamine compound containing a six-membered aliphatic ring.

2. The preparation method according to claim 1, characterized in that: The flexible segment amine compound is selected from at least one of Priamine 1074, Priamine 1075, and polyetheramine T403, and the rigid segment amine compound is selected from at least one of 1,8-diamino-p-menthane, isophoronediamine, and tris(2-aminoethyl)amine.

3. The preparation method according to claim 2, characterized in that: The molar amount of amino groups in the flexible segment amine compound accounts for 20% to 95% of the total molar amount of amino groups in the flexible segment amine compound and the rigid segment amine compound.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the cyclic carbonate in the five-membered cyclic carbonate monomer to the total amount of amino groups in the flexible segment amine compound and the rigid segment amine compound is 1:

1.

5. The preparation method according to claim 4, characterized in that: The rigid group-containing phenolic compound is magnolol, the flexible segment amine compound is selected from tertiary amine compounds with a molecular weight of 400-600 and a polyether structure, and the rigid segment amine compound is selected from short carbon chain tertiary amine compounds with a molecular weight of 100-200.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, stirring a phenolic compound containing a rigid group and epichlorohydrin to react under the action of a first catalyst, and then adding a sodium hydroxide aqueous solution to continue the reaction to obtain a diglycidyl ether intermediate; S2, dissolving the diglycidyl ether intermediate prepared in step S1, the second catalyst, and the co-catalyst in a solvent, placing the mixture in a high-pressure reactor, and reacting the mixture under the condition of introducing CO2 to obtain a five-membered cyclic carbonate monomer; S3, dissolving the five-membered cyclic carbonate monomer prepared in step S2, the flexible segment amine compound, and the rigid segment amine compound in a solvent in proportion for prepolymerization, and obtaining an extreme environment resistant non-isocyanate polyurethane adhesive through post-treatment.

7. The preparation method according to claim 6, characterized in that: The first catalyst in step S1 is at least one of benzyltriethylammonium chloride, tetrabutylammonium chloride and tetrabutylammonium bromide. The second catalyst in step S2 is one of tetrabutylammonium iodide, tetrabutylammonium bromide and tetrabutylammonium chloride, and the co-catalyst is L-ascorbic acid; the solvent is one of N-methylpyrrolidone, acetone and butanone; The solvent in step S3 is at least one of anhydrous chloroform, anhydrous dimethylacetamide, anhydrous dimethylformamide, and anhydrous dimethyl sulfoxide.

8. The preparation method according to claim 6, characterized in that: The molar ratio of the phenolic hydroxyl content in the phenolic compound containing rigid groups to the first catalyst is 1:0.05-0.1; the molar ratio of the phenolic hydroxyl content in the phenolic compound containing rigid groups to epichlorohydrin is 1:20-25; the molar ratio of the phenolic hydroxyl content in the phenolic compound containing rigid groups to sodium hydroxide is 1:1-1.2; The molar ratio of the epoxy group of the diglycidyl ether intermediate to the second catalyst is 1:0.02-0.04, and the molar ratio of the epoxy group of the diglycidyl ether intermediate to the co-catalyst is 1:0.01-0.

02.

9. The preparation method according to claim 6, characterized in that: The stirring reaction conditions in step S1 are 80-100° C. for 2-4 hours, then cooled to room temperature, 40 wt % sodium hydroxide aqueous solution is added through a constant pressure funnel, and the reaction is continued for 1-12 hours; The reaction conditions in step S2 are as follows: pressure 2-4 MPa, 80° C., reaction time 24-48 h; The prepolymerization reaction conditions in step S3 are 70-90° C. for 1-3 hours.

10. A non-isocyanate polyurethane adhesive resistant to extreme environments, characterized in that: The preparation is obtained by the preparation method described in any one of claims 1-4 and 7-9.

Citation Information

Patent Citations

  • Thermoplastic polyurethane elastomer with ultralow temperature resistance and high mechanical property and preparation method of thermoplastic polyurethane elastomer

    CN113980232A

  • Chemically recyclable high-strength non-isocyanate polyurethane and preparation method thereof

    CN115403765A

  • Low-temperature-resistant solvent-free polyurethane adhesive

    CN117050712A

  • Resveratrol-based non-isocyanate polyurethane and preparation method thereof

    CN117586499A

  • High-bonding-strength adhesive with environmental durability and preparation method thereof

    CN117586733A

Cited By

  • Bio-based non-isocyanate polyurethane wood adhesive as well as preparation method and application thereof

    CN121718294A

  • A bio-based non-isocyanate polyurethane wood adhesive, method of making and use

    CN121718294B

  • Starch-based non-isocyanate polyurethane wood adhesive and preparation method thereof

    CN122587645A

  • A starch-based non-isocyanate polyurethane wood adhesive and a preparation method thereof

    CN122587645B